2017
DOI: 10.1111/nmo.13178
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota‐derived tryptophan indoles increase after gastric bypass surgery and reduce intestinal permeability in vitro and in vivo

Abstract: The novel findings are that obese subjects have lower levels of IPA, a solely bacterially derived tryptophan derivative, and IPA improved intestinal barrier function in vitro and DIO mice. Reduced plasma IPA levels and reversal by surgery may be a consequence of intestinal indole-producing microbiota but underlying mechanisms warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 42 publications
6
104
2
2
Order By: Relevance
“…This metabolite and related bacterial compounds (indole-3-aldehyde, indole-3-lactate, and indole-3-propionate) were previously shown to reduce intestinal inflammation and to prevent gut barrier dysfunction (19, 25, 26, 3538). In the present study, we show for the first time that indole alleviates inflammation in the liver, away from the gut.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite and related bacterial compounds (indole-3-aldehyde, indole-3-lactate, and indole-3-propionate) were previously shown to reduce intestinal inflammation and to prevent gut barrier dysfunction (19, 25, 26, 3538). In the present study, we show for the first time that indole alleviates inflammation in the liver, away from the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma IPA amounts were also reported to increase in the same obese model 3 months after Roux-en-Y gastric bypass (RYGB) surgery 64 , indicating, once again, the direct involvement of gut microbiota in the maintenance of the intestinal barrier functions. Furthermore, results from in vitro assays reported by the same authors showed that IPA could reduce the permeability of T84 cell monolayer compromised by pro-inflammatory cytokines 64 .…”
Section: The Role Of Microbiota and Microbiota-derived Dietary Metabomentioning
confidence: 89%
“…Jennis et al . have identified an important role for gut microbiome‐derived tryptophan metabolites, especially IPA, for gut health.…”
Section: Discussionmentioning
confidence: 99%
“…Jennis et al ,. in this issue tested the hypothesis that tryptophan metabolites produced by gut bacteria could reduce intestinal inflammation in high fat diet (HFD) fed mice, in lean human and in obese T2D human patients undergoing Roux‐en‐Y gastric by‐pass surgery for weight loss.…”
Section: Obesity the Gut Microbiome And Tryptophan Metabolismmentioning
confidence: 99%
See 1 more Smart Citation